Marketing Development Strategy for Wealth Management Products to Increase High Net Worth Individual (HNWI) Customers - Rizka Aula Assaf; Eddy Jusup Supardi; Juanim Juanim (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2023)
This study aims to identify, examine and obtain analysis results regarding Retail Banking marketing management, Wealth Management marketing management, factors that may hinder the development of Wealth Management product marketing strategies, Wealth Management service product marketing development strategies in the future carried out by Permata Bank so that Bank Permata can increasing HNWI customers. The research method used is a qualitative method with a single case study approach. The research results show that there are inhibiting factors for the marketing of PermataBank's wealth management services, which consist of internal company factors (employee factors and product limitations factors); and external environmental factors (competitor factors and government regulatory factors). The marketing development strategy for wealth management products is carried out by PermataBank to increase HNWI customers by developing multichannel distribution, expanding strategic partnerships, implementing a strategy to expand the target of millennial customers and increasing the capabilities of frontliners (relationship managers).